Reinforcing interpenetrating network hydrogels with 3D printed polymer networks to engineer cartilage mimetic composites - Kelly, Daniel (My University, 2020)
Engineering constructs that mimic the complex structure, composition and biomechanics of the articular cartilage represents a promising route to joint regeneration. Such tissue engineering strategies require the development of biomaterials that mimic the mechanical properties of articular cartilage whilst simultaneously providing an environment supportive of chondrogenesis. Here three-dimensional (3D) bioprinting is used to develop polycaprolactone (PCL) fibre networks to mechanically reinforce interpenetrating network (IPN) hydrogels consisting of alginate and gelatin methacryloyl (GelMA). Inspired by the significant tension-compression nonlinearity of the collagen network in articular cartilage, we printed reinforcing PCL networks with different ratios of tensile to compressive modulus. Synergistic increases in compressive modulus were observed when IPN hydrogels were reinforced with PCL networks that were relatively soft in compression and stiff in tension. The resulting composites possessed equilibrium and dynamic mechanical properties that matched or approached that of native articular cartilage. Finite Element (FE) modelling revealed that the reinforcement of IPN hydrogels with specific PCL networks limited radial expansion and increased the hydrostatic pressure generated within the IPN upon the application of compressive loading. Next, multiple-tool biofabrication techniques were used to 3D bioprint PCL reinforced IPN hydrogels laden with a co-culture of bone marrow-derived stromal cells (BMSCs) and chondrocytes (CCs). The bioprinted biomimetic composites were found to support robust chondrogenesis, with encapsulated cells producing hyaline-like cartilage that stained strongly for sGAG and type II collagen deposition, and negatively for type X collagen and calcium deposition. Taken together, these results demonstrate how 3D bioprinting can be used to engineer constructs that are both pro-chondrogenic and biomimetic of the mechanical properties of articular cartilage.
PUBLISHED
Keywords: bone marrow-derived stromal cells (BMSCs) and chondrocytes (CCs); Articular cartilage; Tissue engineering; Interpenetrating network hydrogels; Polycaprolactone; 3D bioprinting; Finite element modelling; Biomimetic scaffolds; bone marrow-derived stromal cells (BMSCs) and chondrocytes (CCs)